(untitled) (Agricultural Engineering, 2019)
The aim of the work was to determine the influence of screw speed and variable amounts of fresh vegetable additives on selected aspects of extrusion-cooking of corn-vegetable blends. Corn grit as a basic component was supplemented with a fresh pulp of beetroot, carrot, leek and onion in amounts of 2.5-10% in the recipe. The extrusion-cooking was carried out using a single-screw extruder in the temperature range 120-145°C and extrudates were formed into directly expanded snacks. Two indicators were measured: the production efficiency (Q) and the specific mechanical energy (SME) consumption. As a result of the findings it was noted that the rotational speed of the extruder’s screw showed a greater impact on both production efficiency and SME as compared to the variable amounts of applied additives. A tendency to increased efficiency and specific mechanical energy consumption was observed along with the increase of screw speed during processing. The highest production efficiency was observed if fresh leek and onion were used as additives and the highest extrusion speed screw was applied. The largest specific energy consumption was noted during the extrusion-cooking of blends containing fresh carrot and onion addition at high screw speed.